(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the actual problem - the state personnel in the law enforcement department of the Republic of Kazakhstan. Emphasizes the importance and the role of effective public service in the development of democratic, legal and social state. It is noted that the administrative reform is a priority agenda of Kazakhstan in the new phase of its history. The experience of foreign countries, as well as key problems and contradictions in the existing system of law enforcement, discussed in detail the organization of law-enforcement activity , its inconsistency with the needs of society and the new political and economic conditions of the Republic of Kazakhstan . Particular importance in this article is given to the need to modernize the law enforcement system , which is an important condition for building a rule of law and ensuring internal stability and prosperity. Based on scientific analysis of the formation and development of administrative structures functioning of law enforcement agencies, summarized the organizational and practical measures against corruption, opened the reasons of criminality and public confidence in law enforcement .Emphasizes the importance and the role of political power, political leaders on the reform of personnel policy in law enforcement. Key words: state personnel policy in law enforcement, law enforcement problems in society, modernization of law enforcement.